Pengaruh Budaya Organisasi terhadap Kinerja Keuangan melalui Perilaku Manajer atas Isu Manajemen Lingkungan sebagai Variabel Interveningnya - Vincentius David Djuanda (Business Accounting Review, 2016)
The aim of this study was to know whether there was influence of organizational culture on the company's financial performance through the behavior management on environmental issues. The population used in this study including integration incorporated company PT in Surabaya and Sidoarjo. Samples of this research were the employees who have position as managers. The total sample were 35 respondents and each company represented by 4 managers. This study used path analysis techniques modeling with PLS tools with the applications of SmartPLS. The results from this study was the organizational culture significant and positive influence on the financial performance of incorporated companies PT in Surabaya and surrounding areas.